(untitled) (Intent Research Scientific Journal, 2023)
This article is devoted to the problem of pedagogical technologies as one of the factors influencing the quality of training of specialists in higher educational institutions. The article reveals the features of pedagogical technologies and teaching methods, the conceptual foundations of pedagogical technologies, the concepts of pedagogical technologies in three aspects.